Back Cover: Distinct and independent dielectrophoretic behavior of the head and tail of sperm and its potential for the safe sorting and isolation of rare spermatozoa. Issue 11 (3rd June 2019) - Shuchat, Sholom; Park, Sinwook; Kol, Shahar; Yossifon, Gilad
Abstract : DOI:10.1002/elps.201800437 The cover picture shows a heterogeneous mixture of live sperm, dead sperm (stained with red fluorescent dye) and other cell types enter the microfluidic device. A focusing electrode guides them to the di‐electrophoresis‐based sorting electrode pair. The unwanted cells and debris are repelled by the electrode and leave via the upper channel while the live sperm`s tails (both motile and immotile) are pulled onto the electrodes guiding them to an alternate exit port. The inset shows the electric field intensity distribution. The fields are highest in the gap between the electrodes where the tail is trapped while the head on the other hand is distanced from the potentially harmful electric fields to enable safe sorting.